Hybrid long-range surface plasmon-polariton modes with tight field confinement guided by asymmetrical waveguides - Chen, Jianjun; Li, Zhi; Yue, Song; Qihuang Gong (OPTICS EXPRESS, 2009)
A finite width dielectric-metal-dielectric (DMD) waveguide placed on a substrate is numerically investigated near the telecom wavelength lambda = 1550 nm by the finite element method. With proper waveguide sizes, the asymmetrical DMD waveguide can support hybrid long-range surface plasmon-polariton modes which have tight field confinement (similar to 700 nm) and long propagation lengths (L> 300 mu m) simultaneously. Compact plasmonic waveguide-ring resonators (WRRs) based on such asymmetrical DMD waveguide show high quality factors compared with dielectric-loaded surface plasmon-polariton, channel plasmon polariton, plasmonic whispering-gallery microcavity, and pure dielectric waveguide cases. (C) 2009 Optical Society of America